2006
DOI: 10.1159/000095400
|View full text |Cite
|
Sign up to set email alerts
|

Progesterone and Medroxyprogesterone Acetate Effects on Central and Peripheral Allopregnanolone and Beta-Endorphin Levels

Abstract: The increased use of hormonal therapies has led to the study of the properties of different progestin molecules and their effects on the central nervous system. The central and peripheral levels of neurosteroid allopregnanolone and the opioid peptide β-endorphin (β-END) are regulated by estrogens. The aim of the present study was to investigate the effects of a 2-week oral treatment with micronized progesterone or medroxyprogesterone acetate (MPA) alone or in addition to estradiol valerate (E2V) on central and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
33
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 48 publications
(35 citation statements)
references
References 112 publications
2
33
0
Order By: Relevance
“…We previously showed that the administration of progesterone had a huge impact on the opiatergic system, especially when it was coadministered with an estrogen molecule (10). On the contrary, the neutral effect exerted by DYD suggests a differential impact of this synthetic progestin (when compared with the natural progesterone) on the cell system responsible for the synthesis/release of b-endorphin.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…We previously showed that the administration of progesterone had a huge impact on the opiatergic system, especially when it was coadministered with an estrogen molecule (10). On the contrary, the neutral effect exerted by DYD suggests a differential impact of this synthetic progestin (when compared with the natural progesterone) on the cell system responsible for the synthesis/release of b-endorphin.…”
Section: Discussionmentioning
confidence: 99%
“…Allopregnanolone is a potent endogenous steroid that rapidly affects the excitability of neurons and glia cells through the direct modulation of the activity of g-aminobutyric acid A receptors (5, 6). Allopregnanolone exerts neuropharmacologic actions, with hypnotic/sedative, anxiolytic, anesthetic, and analgesic functions, and it enhances the myelination/remyelination process (7, 8).In addition, it has been demonstrated that chronic intraperitoneal treatment with progesterone or different progestins (medroxyprogesterone acetate [MPA], norethisterone acetate, desogestrel) as well as oral administration of active progestogens (MPA and drospirenone) directly influences the central nervous system's levels of b-endorphin in ovariectomized female rats (3,(9)(10)(11). Beta-endorphin exerts several behavioral, analgesic, thermoregulatory, and neuroendocrine properties (12).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In one recent report, addition of MPA to conjugated equine oestrogens caused an increased insulin resistance in adipose tissue whereas oestrogen alone did not [19]. Bernardi et al [20] found that natural progesterone and MPA do not have the same effects on the expression of central and peripheral allopregnanolone and beta-endorphin levels, suggesting somewhat different receptor mechanisms of action. An in vitro study, Nilsen et al [21] added MPA to a cell culture medium and found increased cytotoxicity and neuronal death after exposure to glutamate.…”
Section: Mpa (Proveramentioning
confidence: 99%
“…Their association with an estrogenic compound does not interfere with the positive effects produced by estrogen on allopregnanolone and beta-END brain content [28]. It was published a case report of a patient with pedophilia who was treated over a 4-year period with medroxyprogesterone acetate (MPA) at a dose of 300 mg/day and as a consequence developed Cushing's Syndrome and adrenal insufficiency, for which he was treated and from which he recovered.…”
Section: Discussionmentioning
confidence: 99%